Development and validation of a self-efficacy scale with writing and social factors - Anaraki Sadegh Soheili, Reza Amirian Seyed Mohammad, Zolfagharkhani Moslem, (Universiti Pendidikan Sultan Idris, 2016)
Development and validation of a self-efficacy scale with writing and social factors by Anaraki Sadegh Soheili, Reza Amirian Seyed Mohammad, Zolfagharkhani Moslem,